Autophagy-Mediated Regulation of Lipid Metabolism and Its Impact on the Growth in Algae and Seed Plants - Yoshitake, Yushi; Ohta, Hiroyuki; Shimojima, Mie (Frontiers in Plant Science, 2019)
Under nutrient starvation conditions, algae and seed-plant cells accumulate carbon metabolites such as storage lipids, triacylglycerols (TAGs) and starches. Recent research has suggested the involvement of autophagy in the regulation of carbon metabolites under nutrient starvation. When algae are grown under carbon starvation conditions, such as growth in darkness or in the presence of a photosynthesis inhibitor, lipid droplets are surrounded by phagophores. Indeed, the amount of TAGs in an autophagy-deficient mutant has been found to be greater than that in wild type under nitrogen starvation, and cerulenin, which is one of the inhibitors of fatty-acid synthesis, induces autophagy. In land plants, TAGs accumulate predominantly in seeds and etiolated seedlings. These TAGs are degraded in peroxisomes via β-oxidation during germination as a source of carbon for growth without photosynthesis. A global analysis of the role of autophagy in Arabidopsis seedlings under carbon starvation revealed that a lack of autophagy enhances the accumulation of TAGs and fatty acids. In Oryza sativa, autophagy-mediated degradation of TAGs and diacylglycerols has been suggested to be important for pollen development. In this review, we introduce and summarize research findings demonstrating that autophagy affects lipid metabolism and discuss the role of autophagy in membrane and storage-lipid homeostasis, each of which affects the growth and development of seed plants and algae.